2012
DOI: 10.1186/1471-2458-12-430
|View full text |Cite
|
Sign up to set email alerts
|

Survival probability and predictors for woman experience childhood death in Nigeria: “analysis of north–south differentials”

Abstract: BackgroundChildhood mortality rate is high in Nigeria. There is dearth of information on the comparison of childhood mortality probability and its causal factors in the Northern and Southern Nigeria. This study was designed to fill these gaps.MethodsNigeria Demographic and Health Survey, 2008 data was used. The first part of this study focused on women aged 15–49 who ever given birth to a child (n = 23,404), irrespective of the survival status of the child and the second part utilized all women aged 15–49 (N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
44
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 13 publications
10
44
2
Order By: Relevance
“…[9][10][11]13 Contrary to the present results, Ettarh and Kimani found that in the rural area in Kenya, household poverty had a significant effect on under-5 mortality, but there was no effect in the urban centers. 17 Other studies showed significant effects of wealth-related variables, such as piped water and ownership of bicycle, radio or tin roof, on infant and child mortality.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…[9][10][11]13 Contrary to the present results, Ettarh and Kimani found that in the rural area in Kenya, household poverty had a significant effect on under-5 mortality, but there was no effect in the urban centers. 17 Other studies showed significant effects of wealth-related variables, such as piped water and ownership of bicycle, radio or tin roof, on infant and child mortality.…”
Section: Discussioncontrasting
confidence: 99%
“…[8][9][10] The strength of the association between household wealth and child mortality depends on the research setting. Several studies showed strong and significant effects of household wealth on child mortality, [11][12][13] while other studies did not detect such effects. [14][15][16] A study from Kenya observed a strong effect of household wealth on child mortality in the rural areas but no effect was shown for children in the urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…The socio-demographic factors influencing infant death are well established in the literature (20,21,22,23,24,25). The infant mortality rate is also a result of ample variety of health and environmental factors such as the child and maternal nutritional status, maternal health knowledge, level of immunization against childhood diseases, income and dietary intake during pregnancy, accessibility to portable water and basic sanitation, etc (26,27 , and birth attendance (None=0, traditional birth attendance=1, unskilled health workers=2, Skilled professionals=3), thus, producing maximum overall score of 11 and 0 as the minimum.…”
Section: Introductionmentioning
confidence: 99%
“…By and large, the prevailing sociopolitical, economic, cultural, and religious differences have translated to varying health care seeking behaviors and demand for health care services in the North and South of Nigeria. The consequence is that maternal and child health indicators are worse off in the northern states compared to the southern states National Population Commission and ICF International 2014;Adebowale, Yusuf, and Fagbamigbe 2012;Bankole et al 2009). …”
Section: Introductionmentioning
confidence: 99%